Electrocoagulation for Treatment of Simulated Blowdown Water Of Cooling Tower (Journal of Engineering, 2020)
This study investigates the results of electrocoagulation (EC) using aluminum (Al) electrodes as anode and stainless steel (grade 316) as a cathode for removing silica, calcium, and magnesium ions from simulated cooling tower blowdown waters. The simulated water contains (50 mg/l silica, 508 mg/l calcium, and 292 mg/l magnesium). The influence of different experimental parameters, such as current density (0.5, 1, and 2 mA/cm2), initial pH(5,7, and 10), the temperature of the simulated solution(250C and 35 0C), and electrolysis time was studied. The highest removal efficiency of 80.183%, 99.21%, and 98.06% for calcium, silica, and magnesium ions, respectively, were obtained at a current density of 1 mA/cm2, initial PH=7, the temperature of 250C and treatment time  60 min. The results have shown the ability of the EC process to remove silica and hardness ions from CTB water.